Typing Style and the Use of Different Sources of Information during Typing: An Investigation Using Self-Reports - Rieger, Martina; Bart, Victoria K. E. (Frontiers in Psychology, 2016)
We investigated to what extent different sources of information are used in typing on a computer keyboard. Using self-reports 10 finger typists and idiosyncratic typists estimated how much attention they pay to different sources of information during copy typing and free typing and how much they use them for error detection. 10 finger typists reported less attention to the keyboard and the fingers and more attention to the template and the screen than idiosyncratic typists. The groups did not differ in attention to touch/kinaesthesis in copy typing and free typing, but 10 finger typists reported more use of touch/kinaesthesis in error detection. This indicates that processing of tactile/kinaesthetic information may occur largely outside conscious control, as long as no errors occur. 10 finger typists reported more use of internal prediction of movement consequences for error detection than idiosyncratic typists, reflecting more precise internal models. Further in copy typing compared to free typing attention to the template is required, thus leaving less attentional capacity for other sources of information. Correlations showed that higher skilled typists, regardless of typing style, rely more on sources of information which are usually associated with 10 finger typing. One limitation of the study is that only self-reports were used. We conclude that typing task, typing proficiency, and typing style influence how attention is distributed during typing.